1974
DOI: 10.1677/joe.0.0600353
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Study of Pituitary-Adrenocortical Response in Mice: Plasma and Brain Corticosterone Determination After Histamine Stress

Abstract: The development of the pituitary-adrenocortical stress response was studied in CBA/J \m=x\ DBA/2J hybrid mice. On the basis of the plasma corticosterone response 15 min after a subcutaneous injection of histamine dihydrochloride (50 mg/kg), the first three neonatal weeks could be divided into stress-nonresponsive (3\ p=n-\ 211 days) and stress-responsive 16\p=n-\21days) periods. During the former period, corticosterone levels in the brains of the non-stressed control mice were 63 % higher than those of compara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

1975
1975
1994
1994

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 10 publications
1
6
0
Order By: Relevance
“…Basal corticosterone levels were constant between postnatal days 10 and 50 which accords with the results of Allen & Kendall (1967) and Kakihana et al (1974), but is in contrast to those of Henning (1978) and Walker et al (1986) who found a marked rise in basal levels between the second and third postnatal week. The absence of stress-induced rises in corticosterone due to saline injection at day 10 confirms results with other stressors where adrenal responses are not apparent at this age (Haltmeyer et al, 1966;Henning, 1978), although recently rises in corticosterone due to ether, electroshock or hypoxia have been demonstrated in 10 day old rat pups (Walker et al, 1986).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Basal corticosterone levels were constant between postnatal days 10 and 50 which accords with the results of Allen & Kendall (1967) and Kakihana et al (1974), but is in contrast to those of Henning (1978) and Walker et al (1986) who found a marked rise in basal levels between the second and third postnatal week. The absence of stress-induced rises in corticosterone due to saline injection at day 10 confirms results with other stressors where adrenal responses are not apparent at this age (Haltmeyer et al, 1966;Henning, 1978), although recently rises in corticosterone due to ether, electroshock or hypoxia have been demonstrated in 10 day old rat pups (Walker et al, 1986).…”
Section: Discussionsupporting
confidence: 87%
“…The absence of stress-induced rises in corticosterone due to saline injection at day 10 confirms results with other stressors where adrenal responses are not apparent at this age (Haltmeyer et al, 1966;Henning, 1978), although recently rises in corticosterone due to ether, electroshock or hypoxia have been demonstrated in 10 day old rat pups (Walker et al, 1986). Also in common with most forms of stress activation (Haltmeyer et al, 1966;Allen & Kendall, 1967;Kakihana et al, 1974), injection causes marked elevations by postnatal day 21. The peak in stress responses at day 40 suggests a late postnatal sensitivity, and a delay in maturation of hypothalamus-pituitary function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, circulating levels of these hormones in nonstressed animals show remarkably little change be tween the second and third week [II, 18,22] and thus it would seem that the capacity for development is intrinsic to the tissue itself and is merely poten tiated by the glucocorticoid hormones. This concept is supported by the stud ies which showed that with increasing age there is a gradual increase in the re sponsiveness of the intestine to pharmacological doses of glucocorticoid.…”
Section: Discussionmentioning
confidence: 99%
“…However the problem with this supposition has been that the majority of the reported values for plasma corticosterone during development are uniformly high from the second through the third postnatal week (66)(67)(68)(69)(70). We raised the question of why the high concentrations of endogenous corticosterone did not elicit intestinal changes during the second week of life and proposed (57,71) that the timing of glucocorticoid action in this system must reflect increased responsiveness of the target cells at the beginning of the third postnatal week.…”
Section: Role Of Hormonesmentioning
confidence: 99%